Leptospira interrogans serovar unipertama isolated in Malaysia - Bahaman, A.R.; Ibrahim, A.L.; Stallman, N.D. (International Union of Microbiological Societies, 1990)
A leptospiral isolate from a bovine kidney was found to be antigenically different from all previously recognized serovars of Leptospira interrogans based on the cross-agglutinin absorption test. The new serovar belongs to the Sejroe serogroup, and the name Leptospira interrogans serovar unipertama is proposed for it, with strain K2-1 as the reference strain.